Understanding Early-Life Adaptive Immunity to Guide Interventions for Pediatric Health - Semmes, Eleanor C.; Chen, Jui-Lin; Goswami, Ria; Burt, Trevor D.; Permar, Sallie R.; Fouda, Genevieve G. (Frontiers in Immunology, 2021)
Infants are capable of mounting adaptive immune responses, but their ability to develop long-lasting immunity is limited. Understanding the particularities of the neonatal adaptive immune system is therefore critical to guide the design of immune-based interventions, including vaccines, in early life. In this review, we present a thorough summary of T cell, B cell, and humoral immunity in early life and discuss infant adaptive immune responses to pathogens and vaccines. We focus on the differences between T and B cell responses in early life and adulthood, which hinder the generation of long-lasting adaptive immune responses in infancy. We discuss how knowledge of early life adaptive immunity can be applied when developing vaccine strategies for this unique period of immune development. In particular, we emphasize the use of novel vaccine adjuvants and optimization of infant vaccine schedules. We also propose integrating maternal and infant immunization strategies to ensure optimal neonatal protection through passive maternal antibody transfer while avoiding hindering infant vaccine responses. Our review highlights that the infant adaptive immune system is functionally distinct and uniquely regulated compared to later life and that these particularities should be considered when designing interventions to promote pediatric health.